New lineage of Triassic aragonitic Foraminifera and reassessment of the class Nodosariata. (1st November 2016) - Rigaud, Sylvain; Vachard, Daniel; Schlagintweit, Felix; Martini, Rossana
Abstract : The new, atypical aragonitic foraminifer Tubulastella comans gen. et sp. nov. is described from the Late Triassic of Panthalassa (Wallowa terrane, north-east Oregon, USA). This rectilinear, undivided tubular form is closely related to ' Coptocampylodon ? rhaeticus ', a Rhaetian incertae sedis commonly found in the western Tethys. Morphologically and structurally distinct from other aragonitic foraminifers, Tubulastella comans gen. et sp. nov. and T. rhaetica gen. et comb. nov. are part of an independent aragonitic lineage, here embodied by the family Tubulastellidae fam. nov. To understand the origination and taxonomic affinity of this unique taxon, a comparative study between Tubulastella and the calcitic syzraniid foraminifer Rectostipulina is carried out. Although these forms differ in wall composition, they present identical constructional patterns, providing evidence of their close phylogenetic relationship. The existence of an aragonitic branch in Nodosariata evolution deeply challenges current foraminiferal classifications and evolutionary hypotheses. We here propose to limit the class Nodosariata to a monophyletic group of bi- to plurilocular foraminifers originating from a Silurian earlandiid ancestor, and the order Nodosariida to a monophyletic lineage of primarily single-layered built foraminifers, which takes root in the Middle Pennsylvanian. This new classification reflects an evolutionary transition from calcitic to aragonitic walls, as documented in other shelled organisms, and definitively excludes calcitic unilocular foraminifers (i.e. Ellipsolagenidae and Lagenidae) from the class Nodosariata. http://zoobank.org/urn:lsid:zoobank.org:pub:D8281D59-38FD-4D88-BEC6-14D5C7B8FD2B